TAX REORIENTATION AS CORRUPTION PREVENTION ON INVESTMENT IN INDONESIA - Henry Dianto Pardamean Sinaga; Anis Wahyu Hermawan (JAF (Journal of Accounting and Finance), 2021)
Investments, that are supposed to increase the country's economic growth and tax revenues, have potentially created "unofficial" costs for investors and unreported informal income of the bribe recipients. It is important to conduct library research using the new institutionalism theory with historical institutionalism approach in answering the main problem. It is concluded that tax reorientation could prevent corruption on investment in Indonesia. The actors involved in investment, even though, will be limited collectively by government organizations, but the existing restrictions are the design of systems that can influence individuals and groups to prevent corruption. Restrictions of the tax authority can be imposed through several ways, such as enforcing bribes as the non-deductible expense and as an income tax object of gifts to the givers, applying bribes as income to the recipients, recommending non-penal sanctions, and blacklisting the individuals or legal entities involved in corruption.